Detection and analysis of DNA mixtures with the MiSeq FGx®. Issue 5 (September 2022) - Gutierrez, Ryan; Roman, Madeline; Houston, Rachel; Kalafut, Tim
Highlights: Sequencing detects isoalleles which offer more information than traditional STR alleles. Y-STRs can help recover minor male genetic information without deconvolution. Peak height ratios for sequencing assays challenge manual deconvolution. Probabilistic software will maximize benefits from sequencing results. Abstract: Recognizing and interpreting mixtures are challenges that occur frequently in forensic casework. Therefore, any new analysis methods that are implemented must handle the challenges of mixed forensic samples. Next generation sequencing offers advantages over capillary electrophoresis in amplicon multiplexing and degraded sample analysis; however, advantages with mixed samples rely heavily on the advancement of user-friendly analysis software. This research analyzed samples with the ForenSeq™ DNA Signature Prep Kit on the MiSeq FGx® and compared them with the GlobalFiler™ STR Kit for capillary electrophoresis. Metrics tested for both chemistries included concordance, limits of detection, and mixture analysis. Data analysis for mixture samples was completed with the MixtureAce™ plug-in and ArmedXpert™ software. Next generation sequencing offered distinct advantages in limits of detection and isoallele heterozygosity but suffered from increased variability in stutter and allele count ratios compared to capillary electrophoresis.